2012
DOI: 10.1017/s0001972011000763
|View full text |Cite
|
Sign up to set email alerts
|

Money and Sociality in South Africa's Informal Economy

Abstract: ABSTRACTThis article examines the interplay of agency, culture and context in order to consider the social embeddedness of money and trade at the margins of South Africa's economy. Focusing on small-scale, survivalist informal enterprise operators, it draws on socio-cultural analysis to explore the social dynamics involved in generating and managing wealth. After describing the informal sector in South Africa, the article elucidates the relationship between money and economic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 28 publications
0
42
0
2
Order By: Relevance
“…Pérez Sáinz () suggests that decisions to operate in IE are not motivated by the desire to be self‐employed, as this is not how women see themselves; informality is chosen for lack of other options because of domestic roles. Similarly, in a longitudinal study in South Africa, Neves and Du Toit () describe women's involvement in business enterprises as motivated by reproductive objectives (sustaining the household, educating children) rather than business development or formalization. Several studies suggest that women's work identity embodies fertility and reproduction, ‘whereby women sow and men plough’ (Laurie , p. 244).…”
Section: Discussionmentioning
confidence: 99%
“…Pérez Sáinz () suggests that decisions to operate in IE are not motivated by the desire to be self‐employed, as this is not how women see themselves; informality is chosen for lack of other options because of domestic roles. Similarly, in a longitudinal study in South Africa, Neves and Du Toit () describe women's involvement in business enterprises as motivated by reproductive objectives (sustaining the household, educating children) rather than business development or formalization. Several studies suggest that women's work identity embodies fertility and reproduction, ‘whereby women sow and men plough’ (Laurie , p. 244).…”
Section: Discussionmentioning
confidence: 99%
“…Also significant is that the scope and scale of informal micro-enterprises continues to grow in most developing countries and South Africa (Neves & Du Toit 2012;Sinha & Kanbur 2012). The reasons for continued growth of South Africa's informal economy and proliferation of micro-enterprises are poorly understood, and there remains a paucity of theorisation.…”
Section: Informality and Shebeens In South Africamentioning
confidence: 99%
“…Counter to the concern with slow or little growth amongst survivalists, Neves and Du Toit (2012) have indicated that township enterprise activities are embedded in a social context where relationships of mutual support and reciprocity can be as important as profit motives, whilst economic participation itself serves a social function and reinforces peoples' sense of belonging, place in community and selfidentity. This argument aligns with institutional theory's tenet that enterprise decisions are influenced by both formal institutions (laws, regulations etc.)…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, it should be recognised that some owners passively accede to the lowly state of their business and have no intention to pursue growth. This is not uncommon in the informal economy where markets are established on a confluence of commercial and social rationales (see Neves & Du Toit 2012). Jane (2399 has run an educare for 4 years and has grown the business from looking after 5 children to 32 children, enabling her to make a profit of R4000 per month.…”
Section: Obstaclesmentioning
confidence: 99%